Florida Solid and Hazardous Waste Regulation Handbook: Pollution Prevention Act (PPA) - Michael T. Olexa; Aaron Leviten; Kelly Samek (EDIS)
The primary purpose of the Pollution Prevention Act is to discourage the disposal of recyclable toxic substances. Under this statute, EPA conducts a yearly audit of the major users of toxic substances and producers of toxic wastes. The purpose of the audit is to determine: whether there are better and less environmentally damaging ways to complete the task without use of toxic substances, whether there are ways to minimize the production of toxic wastes, and whether there are ways to recycle the toxic substances. This is EDIS document FE450, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.